2020
DOI: 10.37796/2211-8039.1021
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium fortuitum and Mycobacterium abscessus infections in the foot and ankle in two immunocompetent patients

Abstract: Nontuberculous mycobacteria (NTM) infections of the musculoskeletal system are commonly missed due to its rarity and the absence of systemic symptoms. A high clinical index of suspicion is required to recognize such infections as they may occur in immunocompetent hosts. We present two cases of foot and ankle NTM infections involving Mycobacterium fortuitum and Mycobacterium abscessus in two such patients. The first case involves an 83-year old lady who presented with a two-month history of multiple foot absces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The language was restricted to English. The literature review showed 6 cases of M. fortuitum complex associated with open fracture infection (Table 2) [1,4,[25][26][27][28]. Osteomyelitis is a known complication of open fracture, but M. fortuitum infections are very rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The language was restricted to English. The literature review showed 6 cases of M. fortuitum complex associated with open fracture infection (Table 2) [1,4,[25][26][27][28]. Osteomyelitis is a known complication of open fracture, but M. fortuitum infections are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Non-tuberculous mycobacteria (NTM), excluding Mycobacterium tuberculosis and Mycobacterium leprae, is an opportunistic pathogen, widely present in natural environments such as water, soil, dust, vegetables, domestic animals, and dairy products [1]. In recent years, the incidence of NTM infections is on the rise worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…To combat the growing clinical burden of multidrug-resistant NTM, novel and repurposed drugs have been tested both in vitro and in vivo. Based on the commonly used anti-NTM antibacterial drugs, 8 drugs were repurposed, namely, vancomycin (VA), bedaquiline (BDQ) (5), delamanid (DLM) (6), faropenem (FAR) (7), meropenem (MPM), clofazimine (CFZ) (8)(9)(10), avibactam (CAZ) (11), and Cefoxitin (FOX) (12) were selected in this study to evaluate drug sensitivity in vitro. These drugs may have antimicrobial activity against different NTM species, although only limited data to support this are available.…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium fortuitum (M. fortuitum) is a fast-growing, gram-positive, opportunistic human pathogen belonging to the nontuberculous mycobacteria (NTM) family that is commonly found in water and soil. NTM infection of the musculoskeletal tissue is a rare disease that may occur in both immunocompetent and immunocompromised individuals; moreover, it is commonly missed or its diagnosis is delayed due to the absence of systemic symptoms and the difficulty involved with isolating the pathogen (Wong et al, 2020;Kasperbauer and Daley, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical procedures are available to deliver antibiotics locally and manage bone defects, with these treatments mainly differing with respect to the material used to fill the defect, such as autologous bone grafting or antibiotic-loaded cement-based grafts (Wassif et al, 2021). Although a few reports have described M. fortuitum osteomyelitis of the cuboid bone (Vasiliadis et al, 2021;Miron et al, 2000;Wong et al, 2020), this is the first case, to our knowledge, in which bone defect restoration has been performed with a single-stage treatment using absorbable, gentamicin-and vancomycin-loaded, calcium sulfate-hydroxyapatite biocomposites.…”
Section: Introductionmentioning
confidence: 99%